Asian G6PD-Mahidol reticulocytes sustain normal Plasmodium vivax development - Bancone, G; Malleret, B; Suwanarusk, R; Chowwiwat, N; Chu, C; McGready, R; Rénia, L; Nosten, F; Russell, B (Oxford University Press, 2017)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common enzymatic disorder in humans and appears to be protective against falciparum severe malaria. Controversially, it is also thought that Plasmodium vivax has driven the recent selection of G6PD alleles. We use an experimental approach to determine whether G6PD-MahidolG487A variant, a widespread cause of severe G6PD deficiency in Southeast Asia, provides a barrier against vivax malaria. Our results show that the immature reticulocytes (CD71+) targeted by P. vivax invasion are enzymatically normal even in hemizygous G6PD-Mahidol G487A mutants; thus allowing the normal growth, development and high parasite density in severely deficient samples.